Deterioration of Automotive Polymeric Materials in Exposed to Pongamia pinnata Biodiesel - Meenakshi, H.N.; Sah, Anish Prasad; Sah, Rajesh (Asian Journal of Chemistry, 2017)
Material compatibility with biodiesels and their blends should be verified on a case-by-case basis to ensure long term durability of storage tanks and pipelines. This paper aimed to investigate the degradation of physical properties such as mass, volume, tensile strength, hardness and change in surface morphology for polymers namely polypthalamide (PPA) and polyarylamide (PAA) upon exposure to Pongamia pinnata biodiesel (PPB) and blends. Static immersion tests in B0, B10, B20 and B100 were carried out at 25, 50 and 75 °C for 120, 360 and 720 h to estimate the degradation behaviour of polymers under static condition. Rotating cage was used to study the degradation behaviour at room temperature for 120 h under flow conditions. Significant changes in the physical properties and surface morphology was observed. The overall compatibility sequence of polymers in Pongamia pinnata biodiesel under static condition was found to be PAA > PPA while under flow condition, the order is and PPA > PAA under flow condition.